Ten years of experience in the prevention of mother-to-child human immunodeficiency virus transmission in a university teaching hospital - Jung-Weon Park; Tae-Whan Yang; Yun-Kyung Kim; Byung-Min Choi; Hai-Joong Kim; Dae-Won Park (Korean Pediatric Society, 2014)
PurposeAdministration of antiretroviral drugs to mothers and infants significantly decreases mother-to-child human immunodeficiency virus (HIV) transmission; cesarean sections and discouraging breastfeeding further decreases this risk. The present study confirmed the HIV status of babies born to mothers infected with HIV and describes the characteristics of babies and mothers who received preventive treatment.MethodsThis study retrospectively analyzed medical records of nine infants and their mothers positive for HIV who gave birth at Korea University Ansan Hospital, between June 1, 2003, and May 31, 2013. Maternal parameters, including HIV diagnosis date, CD4+ count, and HIV ribonucleic acid (RNA) copy number, were analyzed. Infant growth and development, HIV RNA copy number, and HIV antigen/antibody test results were analyzed.ResultsEight HIV-positive mothers delivered nine babies; all the infants received antiretroviral therapy. Three (37.5%) and five mothers (62.5%) were administered single- and multidrug therapy, respectively. Intravenous zidovudine was administered to four infants (50%) at birth. Breastfeeding was discouraged for all the infants. All the infants were negative for HIV, although two were lost to follow-up. Third trimester maternal viral copy numbers were less than 1,000 copies/mL with a median CD4+ count of 325/µL (92-729/µL). Among the nine infants, two were preterm (22.2%) and three had low birth weights (33.3%).ConclusionThis study concludes that prophylactic antiretroviral therapy, scheduled cesarean section, and prohibition of breastfeeding considerably decrease mother-to-child HIV transmission. Because the number of infants infected via mother-to-child transmission may be increasing, studies in additional regions using more variables are necessary.